The evolving profile, role and relevance of the medical director in a pharmaceutical company - Pereira, Carla Raquel Xavier (2018)
Over the last years, operations in Pharmaceutical Companies have become more complex, trying to adapt to new demands of the market environment. Overall, the observed change of paradigm requires adapting, mainly by the setting of new priorities, diversification of investments, cost containment strategies, exploring new markets and developping new sets of skills. In this context, new functions have been created, the relevance of some has diminished, and the importance of others has arisen. Amongst these, the medical structure within a Pharmaceutical Company, increased to meet demands, with companies adopting different models to respond to these needs, and becoming a pillar to the business. Assuming the leading role within a medical department, the medical director function often lies in the shadow. It is a key function within Pharma Industry, either on a country or on a Global basis. It has evolved and changed in the past years to meet the constant demands of a changing environment. The Medical Director is a highly skilled and differeniated professional who provides medical and scientific governance within a Pharmaceutical company, since early stages of drug development and up to loss of exclusivity, not only but also by leading a team of other physicians, pharmacists or life scientists whose functions comprise specificities that the medical director needs to understand, provide input to, oversee and lead. As the organization of Pharmaceutical Companies tends to be different, in accordance to values, culture, markets and strategies, the scope of activities of a Medical Director can be broader or may be limited, depending on size of the organization and governance model, but they must fulfil a large set of requirements in order to leverage impact on internal and internal customers. Key technical competencies for medical directors such as an MD degree, a strong clinical foundation, knowledge of drug development, project and team management experience and written and verbal skills are relatively easy to define, but underlying behavioural competencies are more difficult to ascertain, and these are more often the true predictors of success in the role. Beyond seamless proficiency in technical skills, at this level interpersonal skills become far more important, as they are the driver and the distinctive factor between a good and an excelent medical director. And this has impact in the business and in the people doing it.